Biti direktor v času socializma Med idejami in praksami - Fikfak, Jurij; Prinčič, Jože (Opera ethnologica Slovenica, 2008)
This book ('Company Directors under Communism. Between Ideas and Practice') is the result of a study of archival and other documentary material and interviews with prominent Slovenian company directors from pre-1991 Yugoslavia. It presents the basic structural characteristics and configurations of the communist socioeconomic system in which, despite ideological obstacles, Slovenian entrepreneurship and company directors developed after 1960.